Teachers' Perception on Postmethod Pedagogy in EFL Classes of Nepal - Paudel, Pitambar (Prithvi Academic Journal, 2018)
Discussion on the use of method and postmethod in teaching English has become a debatable issue in Nepal. Many methods emerged as reaction to others claiming each of them as the best one but questions of their practicality and utility led to the development of postmethod pedagogy. This pedagogy empowers teachers' autonomy in the classroom and encourages them to design the best alternative way from the choices on the basis of their experience, knowledge and the context. However, the inclination to method is also on the rise. Supports claim that no practice will be method free. In this context, this study attempts to explore the teachers' perception on postmethod pedagogy in English as Foreign Language (EFL) classes of Nepal. In order to achieve the designated objective, the descriptive phenomenological research design was used and 12 teachers who are teaching English at different schools in Pokhara were purposively selected. The data revealed that teachers have a positive and hopeful experience towards postmethod pedagogy and want to open quality changes in English language teaching, developing context and culture sensitive pedagogy.